Analysis and Detection of Edible Oil Oxidation. Issue 8 (September 2016) - Li, Jinwei; Sun, Xuyuan; Liu, Yuanfa
Abstract : Oxidation of edible oils plays an important role in the flavor, nutrition and safety of foods. This article discusses some of the primary and secondary oxidation products of rancidity and methods used for their detection. New and more precise methods for monitoring the mechanism of oil oxidation are also presented.